Ensino de química para pessoas com deficiência visual: um estudo por meio da revisão sistemática - Toledo, Juliana Barretto de (Universidade Federal de São Carlos, 2017)
Education in Sciences is strongly influenced by the public policies and legislation in course. Among the challenges that the profession demands, is the paradigm of inclusive education, which is even greater when teaching Chemistry, a discipline with a strong visual appeal, for students with visual impairment. As the right to education is not only determined by the access, materialized in the student's enrollment with the school, it is imperative that this student has his permanence, participation and learning ensured throughout his academic life. Some specificities of Chemistry Teaching to visually impaired students have been listed in respect of their educational needs, in order to subsidize the teacher with the means to motivate their student in a way other than visual. The objective of this work was to collect, evaluate and disseminate several studies, with a focus on Chemical Education to students with visual impairment, through the Systematic Review of Literature. The researches were conducted at the Electronic Portals of CAPES, SciELO, BDTD, Web of Science, Scopus and Google Scholar, during the periods of October 2013, March 2014, July 2015 and September 2016. The 256,798 primary studies surveyed were refined in chronological, linguistic and place of publication parameters. After undergoing the systematic procedures, they were classified as "accepted" or "rejected". We retrieved 84 primary studies written in Portuguese and 37 written in English, with free access. The results indicate that Chemical Education is possible for these students, demonstrated by the texts of the studies collected, but that there are still gaps in research about the subject, despite the efforts made by the researchers. Examples of practical work were done, presented and discussed. In order for the teaching of chemistry to reach all students with due equity, the teacher must be prepared and advised by special educators, ensuring quality in the teaching being provided. And to this happens effectively, the government must guarantee through public policies not only the training, but the valuation of these professionals.
Teaching chemistry for people with visual deficiency: an study through the systematic review
Keywords: Ensino de química; Deficiência visual; Revisão sistemática; Chemistry education; Visual impairment; Systematic review; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::ORIENTACAO E ACONSELHAMENTO; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO